Kesempatan Kerja Sektor Informal Di Daerah Perkotaan, Indonesia (Analisis Pertumbuhan dan Peranannya) = Employment Opportunity in Informal Sector in the Urban Areas, Indonesia (The growth and role analysis) - Tadjuddin Noer Effendi (Fakultas Geografi, Universitas Gadjah Mada, 1988)
This paper deals with employment opportunities in the urban areas of Indonesia. The informal sector is present in almost every city in this country. The existence of the informal sector is usually associated with the lack of labour absorption capacity of the formal (modern) sector. The informal sector serves as a buffer against the lack of formal employment opportunities and the consequent unemployment. Nearly one third of the working force in Indonesia cities work in the informal sector Those active in this sector usually are in the fully economically productive age brackets. The Informal sector can serve as a buffer power against the employment opportunity and unemployment. This can be seen from the fact that nearly one third of the working labour in cities work at the informal sector. Whereas, those who are engaged in the informal sector are at the fully productive age.